Prevalence and Influencing Factors of Depression Self-Management Among Chinese Community Residents: A Cross-Sectional Study - Liu, Shuo; Yang, Bing Xiang; Gong, Xuan; Chen, Jie; Liu, Zhongchun; Zhang, Jun; Wang, Xiao Qin (Frontiers in Psychiatry, 2021)
Objective This study aimed to investigate the current status of depression self-management (DSM), and to identify influencing factors of DSM among Chinese community residents. Methods Stratified random sampling methodology was adopted in this cross-sectional survey. Respondents completed a collection of self-administered questionnaires Results The majority of participants were female (72.2%), having a mean age of 39 years (SD = 17.3). The total mean score on the DSSM was low (31.63±4.69). Using multiple linear regression analysis, age ranging from 25-64 years old (Beta = -0.176, p = 0.008), having personal stigma (Beta = -0.143, p = 0.020) and perceived stigma (Beta = 0.127, p = 0.037), and having a nuclear family structure (Beta = -0.313, p = 0.046), good family function (Beta = 0.278, p < 0.001) and good help-seeking attitude (Beta = 0.159, p = 0.008) were associated with DSSM-knowledge. Older age (≥65 years) (Beta = -0.152, p = 0.034), higher CES-D scores (Beta = -0.162, p = 0.005), having a father with a bachelor’s degree or higher level of education (Beta = -0.134, p = 0.047), being female (Beta = 0.147, p = 0.012), indicating a religious preference (Beta = 0.145, p = 0.017) and having good family function (Beta = 0.247, p = 0.001) were significantly associated with DSSM-activities. Conclusions Reducing stigma related to depression and enhancing help-seeking attitudes may be potential strategies for managing depressive symptoms among Chinese community residents.